PENGARUH METODE MIND MAPPING DALAM PEMBELAJARAN DOKKAI PADA MAHASISWA TINGKAT III - Siska Indriawati; Merri Silvia Basri; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstrak: This study discusses the influence of the mind mapping method in learning reading comprehension. In this study, the researchers conducted a study to find out whether there were significant differences in the reading comprehension ability of class 2020 students before and after using the mind mapping method. The type of research used was pre-experimental with the One Group Pretest-Posttest research design. The samples in this study were students of class 2020 of the Riau University Japanese Language Education Study Program with a total of 27 people. Then the material used for the pre-test and post-test was taken from the ふくむすめ童話集小学生童話 website (hukumusume douwa shuu shougakusei douwa), while for the treatment given the material was taken from the Evergreen Japanese Course website.Keywords: Mind Mapping, Dokkai, Eksperimen